Modified Tunnel Technique Combined with Enamel Matrix Derivative: A Minimally Invasive Treatment for Single or Multiple Class I Recession Defects - Vincent-Bugnas, Séverine; Charbit, Yves; Lamure, Julie; Mahler, Patrick; Dard, Michel M. (Journal of esthetic and restorative dentistry, 2015)
Purpose Gingival recession is a significant problem in the esthetic zone. Connective tissue grafts have been considered the gold standard, but they need a donor site that increases morbidity and discomfort for the patient.The purpose of the present study was to evaluate the clinical results of a modified tunnel technique that consists of replacing the connective tissue graft by enamel matrix derivative, in the treatment of Miller Class I recession defects. Materials and Methods Twenty‐six teeth in 14 subjects with Miller Class I recessions were treated using the tunnel procedure plus enamel matrix derivative. The gingival recession, probing depth, clinical attachment level, and the width of the keratinized gingival tissue were recorded. Results There was a statistically significant reduction in gingival recession (88% of root coverage) and a gain in clinical attachment level (3.1 mm) between baseline and 24 months post‐operatively, whereas the change in width of keratinized tissue and in probing depth was not statistically significant. All patients were satisfied with the esthetic appearance and would undergo the same surgery again. Conclusion This technique could be successfully used as an alternative to connective tissue grafts, with the advantage of avoiding the discomfort and morbidity of connective tissue harvesting. Clinical Significance This modified tunnel technique using enamel matrix derivative potentially represents a clinically and esthetically satisfactory treatment of Miller Class I recession defects.